Effect of Preoperative Thoracic Paravertebral Blocks on Emergence Agitation During Tracheal Extubation: A Randomized Controlled Trial - Liu, Wei; Luo, Taijun; Wang, Fei; Zhang, Ding; Liu, Tao; Huang, Jiapeng; Xu, Shaofa (Frontiers in Medicine, 2022)
Objective This study aims to compare the effects of preoperative thoracic paravertebral blocks (TPVB) with intercoastal nerve blocks (ICNB) on emergence agitation (EA) during tracheal extubation in patients who underwent thoracoscopic lobectomy. Design, Setting, and Participants A randomized clinical trial was conducted in patients undergoing thoracoscopic lobectomy at Beijing Chest Hospital between June 2019 and December 2020. Interventions Patients were randomly assigned 1:1 to receive either ultrasound-guided preoperative TPVB or ICNB. Main Outcomes and Measures The primary outcome was the occurrence of emergency agitation, which was evaluated by Aono’s four-point scale (AFPS). Secondary outcomes included hemodynamics [mean arterial pressure (MAP) and heart rate (HR)]; and post-operative pain intensity [visual analog scale (VAS), Ramsay sedation score (RSS), and patient-controlled analgesia (PCA) demand times]. Results Among the 100 patients aged 55–75 years old, 50 were randomized to each group; 97 patients completed the trial. Compared to the ICNB group, the occurrence of EA in the TPVB group was significantly lower [31.3% (15/48) vs. 12.2% (6/49), relative risk = 1.276, 95% CI: 1.02–1.60, P = 0.028]. For patients in the TPVB group, the MAP and HR at 5, 10, and 30 min after extubation were significantly lower; the intraoperative details including emergence time, extubation time, and consumption of sufentanil were significantly shorter than that in the ICNB group. Additionally, patients in the TPVB group showed significantly lower VAS at rest or coughing and significantly lower RSS at 60 and 240 min after extubation than patients in the ICNB group (all P < 0.05). Conclusion Preoperative TPVB was associated with less EA during tracheal extubation when compared with ICNB in patients undergoing thoracoscopic lobectomy. Clinical Trial Registration [http://www.chictr.org.cn/index.aspx], identifier [ChiCTR1900023852].